Implementation of Nawa Cita's 5th Agenda in The Healthy Indonesia Program with a Family Approach - Isasih, Widani Darma; Inayati, Rizqa; Damayanti, Vinna Amalia Resi; Gunawan, Iman (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The Healthy Indonesia Program is one of Nawa Cita's 5th agenda programs to improve the quality of life of Indonesian people. PIS-PK at the Nipah Community Health Center in 2022 has not achieved 100% on all indicators, so an assessment of the input, process and output is needed to determine the implementation of PIS-PK at the Nipah Community Health Center as a first step to finding the root cause of the problem. This research was conducted at the Nipah Community Health Center, using a case study approach with descriptive analysis. The data collection method is through observation, document review and FGD with 6 key informants. The results found that the implementation of PIS-PK on input indicators was still not optimal in the aspects of human resources, facilities and infrastructure, and funding. In the process indicator, further intervention has not been implemented in families that are in the unhealthy category and the IKS output indicator is at 0.16 < 0.80, which means it is in the unhealthy category. So it can be concluded that the implementation of PIS-PK at the Nipah Community Health Center has not been carried out optimally. Keywords: Public, Health, Policy